HATALI İMAL EDİLEN MİL ÇAPLARININ, L2 TİPİ KEÇE ÖMÜRLERİ ÜZERİNE OLAN ETKİLERİNİN ARAŞTIRILMASI - ÖZEL, CİHAN (Fırat Üniveristesi, 1993)
Bu çalışmada, L2 tipi bir yağ keçesinin, hatalı imal edilen mil çaplarında, farklı mi hızlarında, kuru, yağlı ve farklı yağ basınçlarının sağlandığı ortamlarda ömürleri araştırıldı. Bu amaç için bir deney seti hazırlanarak, 250. 000, 500,000, 750.000 ve 1.000.000, toplam devirlerde, keçe dudaklarında meydana gelen aşınmalar ve sıcaklıklar ölçülerek, değişim grafikleri çizildi.

In this studay.The life of OToilse^'mtypeof L2wasawestigated'mshaft diameters which were produced In the wrong, in different shaft speeds, in dry, c% and different 08 pressures for this purpose, an experimental set was constructed corrosions in seal up and heat in the total periods of 250.000, 500.000, 7S0.000, and 1.000.000, were meausured and then graphics of variations was drawn.
An Investigation of the effects on the L2 type seal lifes of erroneously manufactured shaft diameters
Keywords: Makine Mühendisliği; Mechanical Engineering